An Assessment of Grant‐based Multilateral Funding Flows from 2014 to 2016. Issue 2 (3rd March 2019) - McArthur, John W; Rasmussen, Krista
Abstract: This paper presents a global snapshot of how all countries, plus the Bill & Melinda Gates Foundation, allocated approximately $63 billion per year across 54 major multilateral organizations during the 2014–16 period. We assess direct funding to United Nations and non‐UN organizations to examine three key questions. First, how much does each funder contribute to each organization? Second, what is the relative importance of each funder to each organization? Third, how do funding allocations compare to objective benchmarks like share of donor country income, share of world income and share of world population? We find that a small number of countries provide a majority of total funding and a small number of organizations account for a majority of total resources received. Only a handful of countries are the top funders to at least one organization, but a variety of mid‐ and smaller‐sized economies play larger relative roles in some smaller organizations. Estimating funders' flows across organizations allows for assessment of their revealed preferences among multilateral priorities and enables comparison against objective benchmarks for burden‐sharing. To our knowledge, this is the first study to provide a comprehensive mapping of all countries' recent annual grant funding across the majority of large multilateral institutions. Abstract : Future research could usefully unpack underlying streams of finance to each entity and investigate how funding flows have changed over time, potentially reflecting shifts in priorities.